Effect of Discharged Industrial Water from Tannery Plants in Nahrawan on Groundwater and Brick Quarries Soil - Hashim, Bassim Mohammed; Abdulraheem, Esam; Abdali, Haider Sattar (Iraqi Journal of Science, 2018)
The discharged water from tannery plants is main source for pollution of soil and groundwater, especially in Nahrawan area. Water samples is collected from 10 sites of wells, discharged water and from using water in different levels of tannery and 7 soil samples from different sites inside factories area and outside it. The results shown that pH for samples of wells and discharged water were within allowable limits between 6.5- 8.5, except the value of pH recorded in the discharged water sample (after the addition of calcium hydroxide) was 12.8, as well as reached the highest value of total dissolved salts (TDS) 7800 ppm in same samples. It also reached its highest value of electrical conductivity (EC) 8200 μS/cm. The results showed that most samples of discharged water recorded high values of turbidity reached to 557 NTU, while the lowest values recorded in water wells and water sample of Nahrawan village. The samples of discharged water was contained high concentration of relatively heavy elements (Pb and Ni), while not sensing concentration of (Cd and Cr), especially for non-use of chromium in the tanning process because of the lack of economic viability by the owners of the factories. The results of analysis of heavy elements in the soil samples to the concentration of Pb in the samples were all within the limits of Iraqi standard was 50-300 ppm. The results indicated that the highest concentration of Ni recorded in samples of soil in the east and south-eastern tanneries exceeding the Iraqi standard concentration of Ni in the soil the amount of 30-75 ppm, while the concentration of Ni in other soil samples was within the limits of the Iraqi standard, while not sensing by concentration of (Cd and Cr) in these samples.